Cardiorespiratory fitness as predictor of cancer mortality: a systematic review and meta-analysis - Schmid, D; Leitzmann, M F (Annals of oncology, 2015)
Epidemiologic studies have reported that cardiorespiratory fitness is inversely associated with mortality from cancer. However, the evidence relating cardiorespiratory fitness to cancer mortality has not yet been quantitatively summarized. Following the preferred reporting items for sytematic reviews and meta-analyses (PRISMA) checklist, we conducted a systematic review and meta-analysis of the association between cardiorespiratory fitness and total cancer mortality. Relevant studies were identified through a literature search in PubMed up to August 2013 and by screening reference lists of qualifying articles. Data extraction was carried out independently by both authors and summary risk estimates were obtained using random-effects models. Six prospective studies with an overall number of 71 654 individuals and 2002 cases of total cancer mortality were included. The median follow-up time in the studies was 16.4 years. Cardiorespiratory fitness showed a strong, graded, inverse association with total cancer mortality. Using low cardiorespiratory fitness as the reference group, intermediate and high levels of cardiorespiratory fitness were related to statistically significant decreased summary relative risks (RRs) of total cancer mortality of 0.80 [95% confidence interval (CI) 0.67-0.97] and 0.55 (95% CI 0.47-0.65), respectively. Studies that adjusted for adiposity yielded similar results to those that did not adjust for adiposity. Increased cardiorespiratory fitness represents a strong predictor of decreased total cancer mortality risk, independent of adiposity.